Characteristics of Pure Oils from Belly Fat (Pangasius hypophthalmus) with Bentonite Purification - Lorde Sembiring; Mirna Ilza; Andarini Diharmi (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Catfish (Pangasius hypophthalmus) processing industry produces by products of abdoment fat containing unsaturated fatty acids, polyunsaturated fatty acids (PUFAs) which are the essential fatty acids needs to maintain health. Catfish belly fat can be processed into coarse fish oil through a purification process, with the addition of the adsorbent used, one of which is bentonite. This study was aimed to determine theeffect of bentonite application on the characteristics of refined catfish oil. Fish oil was extracted from belly fat then purified by adding bentonite adsorbent at a concentration of 1; 4 and 7%. The design used in thisstudy was a complete factorial of one factor. The parameters of analysis were the number of free fatty acids, peroxide value, anisidine, and totox. The results showed that bentonite had significant effect on free fattyacid, peroxide, anisidine and totox values. The use of 7% bentonite decreased content of free fatty acid, peroxide value, anisidine, peroxide and totox from 1.72 to 0.85%, 5.18 to 0 meq/kg, 27.51 to 2.28 meq/kg,and 37.88 to 2.28 meq/kg respectively.